On the Biocompatibility and Teat Retention of In Situ Gelling Intramammary Formulations: Cattle Mastitis Prevention and Treatment - Sushila Bhattarai; Dhayaneethie Perumal; Michael J. Rathbone; Craig R. Bunt; Raid G. Alany (Pharmaceutics, 2021)
Treatment and prevention of cattle mastitis remains a formidable challenge due to the anatomical and physiological constraints of the cow udder. In this study, we investigated polymeric excipients and solvents that can form, (when combined) novel, non-toxic and biocompatible in situ gelling formulations in the mammary gland of bovine cattle. We also report on a new approach to screen intramammary formulations using fresh excised cow teats. Fourteen hydrophilic polymers and six solvents were evaluated for in vitro cytotoxicity and biocompatibility towards cultured bovine mammary epithelial cells (MAC-T), microscopic and macroscopic examination upon contact with excised cow teats. No significant cytotoxicity (p > 0.05) was observed with polyethylene oxides, hydroxypropyl methylcellulose, carboxymethyl cellulose, sodium alginate and xanthan gum. Polycarbophil and carbopol polymers showed significantly higher cytotoxicity (p < 0.05). Concentration-dependent cytotoxicity was observed for glycerin, propylene glycol, polyethylene glycol 400, ethanol, N-methyl-2-pyrrolidone and 2-pyrrolidone, with the 2-pyrrolidone solvents showing higher cytotoxic effects (p < 0.05). In situ gelling formulations comprising hydroxypropyl methylcellulose or carboxymethyl cellulose and solvents in specific ratios were biocompatible at higher concentrations with MAC-T cells compared to alginates. All investigated formulations could undergo in situ sol-to-gel phase transformation, forming non-toxic gels with good biocompatibility in excised cow teats hence, showing potential for use as intramammary carriers for sustained drug delivery.